Density and width-weight relationship of blue swimming crab (Portunus pelagicus) in Letman Waters, Southeast Maluku - Silaban, Ade (Acta Aquatica: Aquatic Sciences Journal, 2022)
Blue swimming crab (Portunus pelagicus) is a fishery commodity with a fairly high selling value, both as a local commodity and as an export commodity. The high level of utilization and trade of blue swimming crabs is not matched by knowledge of how to conserve these resources so that it can result in a decrease in blue swimming crab resource stocks. Sampling was carried out in November 2021 using a selected random sampling method. The density of the male blue swimming crab is 94,118 ind/km2 and the female is 58,824 ind/km2. The results of the analysis of the width-weight relationship of the blue swimming crab showed the nature of the blue swimming crab growth was negative allometric with a b value of 2.579.Keywords: blue swimming crab; density; Letman; width-weight relationship